Vascoda and the Subject-based Gateways - the German Answer to Visibility and Accessibility in Collection Development - Kempf, Klaus (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
The „classic tasks“ of academic libraries comprise acquisition, cataloguing, reader services and preservation of literature or, more generally speaking, information resources. This has not changed radically in the digital age. What has changed, though, is the way the tasks are related to each other, perhaps also their respective importance (depending on the library type); but particularly the accentuation of certain aspects of the tasks mentioned above. Visibility and accessibility would hardly have been associated with collection development in the past. Holdings were entered in the catalogue and thus made ‘visible’. Accessibility was taken care of in the reader services department. This has changed significantly in the digital age. The reasons for that are manifold: · With the emergence of the so called ‘hybrid library’ the respective tasks of the central library functions have somewhat shifted and the previously rather clear-cut separations between them have become less rigid. · The innate ‘immateriality’ of digital resources requires a different approach to the topic of visibility and accessibility as early as the actual point of acquisition and in the presentation and ‘documentation’ of collection development. · Last but not least digital access points, next to the catalogue or OPAC including a large variety of different options (e.g. websites), have led to a much quicker and easier way of making holdings and particularly new acquisitions visible than would have been possible in the days of paper or card catalogues. But there are more basic reasons for the new way of dealing with visibility and accessibility. This is certainly due to the characteristics of collection development in the digital age which require us ‘acquisitions people’ to look at the question of visibility and accessibility from a different perspective and regard these as key aspects of the work we do.